Are immigrants more vulnerable to the socioeconomic impact of COVID-19? A cross-sectional study in Amadora Municipality, Lisbon metropolitan area - Maria, Maria Rosario (2022)
Funding Information: The project was funded by a grant from the Portuguese Science and Technology Foundation (FCT), RESEARCH4COVID19, reference 065, co-financed by FAMI funds reference PT/2018/FAMI/350, and by Saúde Global e Medicina Tropical, Instituto de Higiene e Medicina Tropical, Universidade NOVA de Lisboa, Portugal, ref. UID/04413/2020. Publisher Copyright: Copyright © 2022 O. Martins, Shaaban, Abecasis, Muggli, Amado, Vaz, Dias, Silva and Fronteira.